Diversifikasi Limbah Air Kelapa Menjadi Sirup, Cuka, Nata De Coco (SICUKO) Di Desa Katumbangan Lemo - Maulida Nurdin, Gaby; Wahid, Masyitha; Amaliah, Nur (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Purpose – The purpose of this activity is to assist partner business groups in optimizing the processing of coconut water waste into diversified products such as syrup, vinegar, and nata de coco (SICUKO). Design/methodology/approach – The implementation method includes preparation stages, implementation stages involving socialization, training, and mentoring, as well as an evaluation stage. Findings – Training activities are conducted by producing outputs such as syrup, vinegar, and nata de coco products from packaged coconut water, labeled, and ready for marketing or consumption. The evaluation results show a significant improvement in participants' knowledge regarding the coconut water processing into SICUKO processed products before and after the activity. Additionally, participants appreciate the taste, aroma, and texture of the products produced based on organoleptic test results. Originality/value – Through this community partnership stimulus program, we can address the coconut water waste issue that has already had an impact on the environment by generating economically valuable products, especially since coconuts are the main commodity in the Katumbangan Lemo Village.